2022
DOI: 10.3390/ijms23031231
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risky Choice and Reduced CHRNB2 Expression in Adult Male Rats Exposed to Nicotine Vapor

Abstract: While the cognitive enhancing effects of nicotine use have been well documented, it has also been shown to impair decision making. The goal of this study was to determine if exposure to nicotine vapor increases risky decision making. The study also aims to investigate possible long-term effects of nicotine vapor exposure on the expression of genes coding for cholinergic and dopaminergic receptors in brain. Thirty-two adult male Sprague Dawley rats were exposed to 24 mg/mL nicotine vapor or vehicle control, imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The pairs of rats were derived from the same group condition (i.e., a female adolescent with another female adolescent) and they remained with the same partner throughout the exposure procedure. Our decision to use ambient air for the control condition was based on previous studies from our laboratory showing that PG/VG elicits behavioral effects, such as changes in riskiness, that could impact our assessments of approach behavior (Giner et al, 2022). Other laboratories have also used ambient air as a control condition in nicotine vapor studies in rats (Gilpin et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The pairs of rats were derived from the same group condition (i.e., a female adolescent with another female adolescent) and they remained with the same partner throughout the exposure procedure. Our decision to use ambient air for the control condition was based on previous studies from our laboratory showing that PG/VG elicits behavioral effects, such as changes in riskiness, that could impact our assessments of approach behavior (Giner et al, 2022). Other laboratories have also used ambient air as a control condition in nicotine vapor studies in rats (Gilpin et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, higher levels of nAChR binding were significantly associated with less risky choice in a probability-discounting task, indicating cholinergic systems are involved in risky decision making (Mendez et al ., 2013). Both exposure to 24 mg/ml nicotine vapor (Giner et al ., 2022) and acute 1.0 mg/kg nicotine administration (Mendez et al ., 2012) increased choice for the larger, uncertain reinforcer in a probability-discounting procedure in rats. These increases in risky choice may be due to nicotine’s effects on response perseveration, or persistent choice for an option despite changing contingencies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently reported that nicotine vapor exposure impairs the risk-based decision making in adult rats [21]; our previous work indicated that menthol flavor in e-cigarette vapor increases social behaviors in mice [22]. The potential mechanisms may include nicotine-related alterations of neurotransmitters and chemicals that signal inflammation in certain brain regions, such as the decreased dopamine concentration in the striatum and GABA in the frontal cortex, while increased levels of glutamate in the striatum and glutamine in the frontal cortex and striatum by chronic inhalation of e-cigarette vapor containing nicotine [23]; the reduced gene expression of Ngfr and Bdnf, and increased expression of IBA-1, a specific marker of microglia in the hippocampus [24]; changes on the CNS development-related gene profile in the frontal cortex [25]; and cytokines such as interleukin IL-4 and interferon-gamma (IFN-γ) in the diencephalon, as well as levels of hippocampal IFN-γ, and IL-6 in the cerebellum in the offspring of mice exposed prenatally to e-cigarette aerosols [26].…”
Section: Introductionmentioning
confidence: 99%
“…The reductions on the CHRNB2 in the nucleus accumbens and the medial prefrontal cortex (mPFC) [21], and increased α-7 nicotinic acetylcholine receptor in the frontal cortex (FC) and striatum (STR) [27], were observed in animal models administrated with chronic nicotine vapor. However, it is unclear how the immune system in the brain affects the expression of nicotinic receptors as well as the activities of the related neural circuits to mediate alterations in cognition and psychiatric behaviors.…”
Section: Introductionmentioning
confidence: 99%